Development of Crenosoma vulpis in the common garden snail Cornu aspersum: implications for epidemiological studies. Issue 1 (December 2016) - Colella, Vito; Mutafchiev, Yasen; Cavalera, Maria; Giannelli, Alessio; Lia, Riccardo; Dantas-Torres, Filipe; Otranto, Domenico
Abstract Background Crenosoma vulpis (Dujardin, 1845), the fox lungworm, is a metastrongyloid affecting the respiratory tract of red foxes (Vulpes vulpes ), dogs (Canis familiaris ) and badgers (Meles meles ) living in Europe and North America. The scant data available on the intermediate hosts ofC. vulpis, as well as the limited information about the morphology of the larvae may jeopardise epidemiological studies on this parasite. Methods Suitability and developmental time ofC. vulpis in the common garden snailCornu aspersum (=Helix aspersa ) was assessed at selected days post-infection (i.e. 3, 6, 10, 15, 20 and 180). Nematodes were preserved in 70 % ethanol, cleared and examined as temporary mounts in glycerol for morphological descriptions of first- and third-stage larvae. In addition, nematodes collected from the dog and the experimentally infected snails were molecularly analysed by the amplification of the nuclear 18S rRNA gene. Results Specimens ofC. aspersum digested before the infection (n  = 10) were negative for helminth infections. Out of 115 larvae recovered from infected gastropods (mean of 9.58 larvae per snail), 36 (31.3 %) were localised in the foot and 79 (68.7 %) in the viscera. The 18S rDNA sequences obtained from larvae collected from the dog and the snail tissues displayed 100 % identity to the nucleotide sequence ofC. vulpis . Conclusions Cornu aspersum is herein reported for the first time as a suitable intermediate host ofC. vulpis . This snail species may play an important role for the infection of animals living in regions of the Mediterranean basin. In addition, this study provides more details on the morphological descriptions of L1 and L3 and supports future investigations on the epidemiology of this little known parasite.